Workload monitoring in top-level soccer players during congested fixture periods - Gualtieri, A.; Rampinini, E.; Sassi, R.; Beato, M. (International Journal of Sports Medicine, 2020)
This study assessed the internal and external workload of starters and non-starters in a professional top-level soccer team during a congested fixture period. Twenty Serie A soccer players were monitored in this study during two mesocycles of 21 days each. Starters and non-starters were divided based on the match time played in each mesocycle. The following metrics were recorded: exposure time, total distance, relative total distance, high-speed running distance over 20 km·h-1, very high-speed running distance over 25 km·h-1, individual very high-speed distance over 80% of maximum peak speed, and rating of perceived exertion. Differences between starters and non-starters were found for: exposure time (effect size=large to very large), rating of perceived exertion (large to very large), total distance (large to very large), and individual very high-speed distance over 80% of maximum peak speed (moderate to large). Furthermore, differences for relative total distance, high-speed running distance over 20 km·h-1 and very high-speed running distance over 25 km·h-1 were small to moderate, but not significant. This study reports that during congested fixture periods, starters had higher exposure time, rating of perceived exertion, total distance, and individual very high-speed distance over 80% of maximum peak speed than non-starters